Successful user experience : strategies and roadmaps - Rosenzweig, Elizabeth (Morgan Kaufmann, 2015)
Successful User Experience: Strategy and Roadmaps provides you with a hands-on guide for pulling all of the User Experience (UX) pieces together to create a strategy that includes tactics, tools, and methodologies. Leveraging material honed in user experience courses and over 25 years in the field, the author explains the value of strategic models to refine goals against available data and resources. You will learn how to think about UX from a high level, design the UX while setting goals for a product or project, and how to turn that into concrete actionable steps. After reading this book, you'll understand: How to bring high-level planning into concrete actionable steps How Design Thinking relates to creating a good UX How to set UX Goals for a product or project How to decide which tool or methodology to use at what point in product lifecycle This book takes UX acceptance as a point of departure, and builds on it with actionable steps and case studies to develop a complete strategy, from the big picture of product design, development and commercialization, to how UX can help create stronger products. This is a must-have book for your complete UX library. Uses strategic models that focus product design and development Teaches how to decipher what tool or methodology is right for a given moment, project, or a specific team Presents tactics on how to understand how to connect the dots between tools, data, and design Provides actionable steps and case studies that help users develop a complete strategy, from the big picture of product design, development, and commercialization, to how UX can help create stronger products Case studies in each chapter to aid learning.